2015
DOI: 10.5433/1679-0359.2015v36n3supl1p2317
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de vacas leiteiras alimentadas com cana de açúcar associada à ureia e tratada com cal virgem na região do Alto Pantanal Sul-Mato-Grossense

Abstract: ResumoAvaliou-se o efeito do uso de dietas contendo cana de açúcar in natura e associada com ureia e/ou cal virgem, sobre o desempenho produtivo, composição do leite e digestibilidade dos alimentos em vacas leiteiras da raça Girolando. O experimento teve duração de 84 dias. Os animais foram mantidos confinados em sistema tie stall e receberam os seguintes tratamentos: Cana in natura (Ca); Cana in natura com Ureia (CaUr); Cana hidrolisada com Cal Virgem (CaCal) e Cana hidrolisada com Cal Virgem mais Ureia (CaUr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…These were the only studies on lactating cows in which there was any change in milk production or composition due to the inclusion of hydrolyzed sugarcane. The milk yields and compositions observed in the present study are within the ranges reported in previous studies in which sugarcane hydrolyzed with CaO was supplied to lactating cows: 7.29-19.98 kg milk cow −1 day −1 with 2.96%-3.41% protein, 3.23%-4.32% fat, 4.09%-5.63% lactose, and 11.22%-13.00% total solids (CARVALHO, 2008;SFORCINI, 2009;SILVA JÚNIOR et al, 2015;TEIXEIRA JUNIOR et al, 2015).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…These were the only studies on lactating cows in which there was any change in milk production or composition due to the inclusion of hydrolyzed sugarcane. The milk yields and compositions observed in the present study are within the ranges reported in previous studies in which sugarcane hydrolyzed with CaO was supplied to lactating cows: 7.29-19.98 kg milk cow −1 day −1 with 2.96%-3.41% protein, 3.23%-4.32% fat, 4.09%-5.63% lactose, and 11.22%-13.00% total solids (CARVALHO, 2008;SFORCINI, 2009;SILVA JÚNIOR et al, 2015;TEIXEIRA JUNIOR et al, 2015).…”
Section: Resultssupporting
confidence: 90%
“…In general, this is the result that has been systematically observed in the few studies performed on lactating cows fed diets based on sugarcane hydrolyzed with CaO. Illustrating this, Carvalho (2008) and Silva Júnior et al (2015) did not observe a positive effect (P>0.05) of sugarcane hydrolysis for 24 h with 0.75% to 2.25% CaO on the digestibility of DM, OM, CP, NDF and TDN. Similarly, there was no effect (P>0.05) on DM, CP, NDF, NDFap, ADF and TDN intake in diets based on sugarcane hydrolyzed for up to 48 h with 0.5% to 2% CaO (CARVALHO, 2008;SFORCINI, 2009;SILVA JÚNIOR et al, 2015;TEIXEIRA JUNIOR et al, 2015).…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…Sugarcane (Saccharum officinarum) is used in cattle feed in the tropical climate owing to its high production of dry materno (DM) (Silva Junior et al, 2015). Sugarcane in natura requires daily management, which increases the cost and hampers the management of the farm, especially the feedlots (Andrade, 2013;Siqueira et al, 2012).…”
Section: Introductionmentioning
confidence: 99%